ANALYSIS OF FACTORS INFLUENCING THE PROFITABILITY OF ISLAMIC BANKING - Dhita A'ulia Syamsi; Anton Bawono (MESP–FEB UNS, 2024)
This study uses a quantitative approach to analyze the influence of operational costs and income, non-performing financing (NPF), and the Islamicity Performance Index on the profitability of Islamic banking, with intellectual capital as a moderating variable. The population includes Sharia Commercial Banks located in Indonesia and registered with the Financial Services Authority from 2015 to 2022. The sample was determined using purposive sampling, resulting in 56 data points. Hypotheses were tested using Moderated Regression Analysis (MRA) with Eviews 12 software.The results indicate that operational costs and income (BOPO) significantly influence the Return on Assets (ROA), while NPF does not. The profit-sharing ratio (PSR) and the Islamic Income vs Non-Islamic Income Ratio (IsIR) significantly influence ROA. Intellectual capital (IC) has a direct influence on ROA but does not moderate the relationship between BOPO and ROA, nor between NPF and ROA. However, IC can moderate the relationship between the profit-sharing ratio and ROA. It does not moderate the relationship between IsIR and ROA. These findings suggest that operational efficiency, profit-sharing mechanisms, and the proportion of Islamic income are crucial for enhancing profitability in Sharia Commercial Banks, with intellectual capital playing a significant but selective moderating role.